‘EDICTUM CLAUDII DE CIVITATE VOLUBILITANORUM’ - Jurewicz, Aldona Rita; Tadajczyk, Konrad Tomasz (Zeszyty Prawnicze, 2016)
‘EDICTUM CLAUDII DE CIVITATE VOLUBILITANORUM’ Summary ‘Edictum Claudii de civitate Volubilitanorum’ is an inscription placed on the pediment of the statue dedicated to Marcus Valerius Severus, son of Bostar. He was the commander of the auxiliary units during the war against Aedemon. The statue was set up by Valerius’s wife Fabia Bira. The inscription contains enumeration of the privileges having been granted by Claudius to the inhabitants of Volubilis. This bestowal of rights appears to have been the emperor’s acknowledgment of the assistance the inhabitants of Volubilis rendered the Romans against Aedemon’s rebellion after the death of Ptolemy, the last king of Mauretania. The rebels rose up following the murder of their king by Caligula and the subsequent incorporation of their country in the Roman Empire. However, the Volubilians supported the Romans. The emperor granted them Roman citizenship and the right to marry nonRoman women, while the town itself was allowed to acquire the estates of inhabitants who had died without leaving an heir (bona vacantia).